Michele Giua: libertà e morale di un chimico socialista - Nicolini, Nicoletta (Chimica nella Scuola, 2022)
A portrait of the chemist Michele Giua, engaged in teaching and research at the University and then in parliamentary activity, forced to eight years of suffering in captivity. A man with a prodigious memory, which allowed him as a prisoner to write scientific books and then to successfully counter the arguments of his opponents. The polite polemical system of Michele Giua was evident in his observations as a man of science even in the parliamentary sphere. Considered a master by his colleagues for wisdom, extreme rigor, high moral conscience, he was engaged in creating a fairer society, maintaining a deep faith in socialism and freedom as essential condition of higher morality.